2019
DOI: 10.5897/jco2019.0193
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NPSZnB fertilizer levels on yield and yield component of maize (Zea mays L.) at Laelay Adiyabo and Medebay Zana districts, Western Tigray, Ethiopia

Abstract: The use of right amount of fertilizer based on crop requirement has a significant importance for sustainable crop production. Study was undertaken to investigate the effects of NPSZnB blended fertilizer for maize yield production at Laelay Adiyabo and Medebay Zana districts. Seven treatments were used for the field experiment. Treatments were without fertilizer, blanket recommended NP (64 kg N ha -1 +69 kg P 2 O 5 ha -1 ) and five treatments of blended fertilizer rates (150, 200, 250, 300, and 350 kg NPSZnB ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…The increase in the harvest index due to the application of micronutrients may be attributed to their role in enhancing the photosynthesis process and translocation of photosynthetic products to the economic part. Generally, application of blended fertilizers had significant effects on the harvest index of maize crop than recommended N and P. This result agrees with the findings of previous study 17 who reported that harvest index of teff was found to be highest in blended fertilizer treatments. This report was also slightly similar with 18 those reported the harvest index of maize was found to be significantly higher in plots that received blended fertilizers at a rate of 150 kg NPSZnB haG 1 as contrasted to the control treatment but, it was signed in par with 300 kg NPSZnB haG 1 and recommended NP fertilizers.…”
Section: Resultssupporting
confidence: 91%
“…The increase in the harvest index due to the application of micronutrients may be attributed to their role in enhancing the photosynthesis process and translocation of photosynthetic products to the economic part. Generally, application of blended fertilizers had significant effects on the harvest index of maize crop than recommended N and P. This result agrees with the findings of previous study 17 who reported that harvest index of teff was found to be highest in blended fertilizer treatments. This report was also slightly similar with 18 those reported the harvest index of maize was found to be significantly higher in plots that received blended fertilizers at a rate of 150 kg NPSZnB haG 1 as contrasted to the control treatment but, it was signed in par with 300 kg NPSZnB haG 1 and recommended NP fertilizers.…”
Section: Resultssupporting
confidence: 91%
“…From the result, as plant population increased the plant and ear height of BH546 Maize hybrid increased linearly. Similarly, Tekulu et al (2019) [47] reported that plant height of maize was significantly influenced by NPSZnB levels in Laelay Adiyabo district but not in Medebay Zana district. Plant growth and development probably retarded if any of the nutrient is under its threshold value in the soil or not sufficiently balanced with other nutrient.…”
Section: Maize Growth Development and Yield Characters 311 Maize Plan...mentioning
confidence: 92%
“…High N and P nutrient elongates basal internode which in turn maximize the ear and plant height of maize (Rajkumara 2008) [42] . Moreover, increment in plant height is probably due to increase in cell elongation and greater vegetative growth at the return of different nutrient contained in NPSZnB fertilizer contribute for plant growth (Tekulu et al, 2019) [47] . Higher plant population density lead to the weaker plants of more height (Chandiposha and Chivende, 2014) [12] .…”
Section: Maize Growth Development and Yield Characters 311 Maize Plan...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main rainy season with high rainfall intensity, which is locally called kiremit, extends from July to September with a unimodal rainfall pattern. The annual amount of rainfall ranges from 500 to 937 mm ( Kinfe et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%